Counter-colonial criminology : a critique of imperialist reason - Agozino, Biko (Pluto Press, 2003)
'A groundbreaking book ... [offering] dazzling brilliance in the development of criminological theory.' Ihekwoaba D. Onwudiwe, Associate Professor, University of Maryland Eastern Shore.
Keywords: Criminology.; Imperialism.; Criminologie.; Impérialisme.; criminology.; SOCIAL SCIENCE -- Criminology.; POLITICAL SCIENCE -- Human Rights.; Criminology; Imperialism